Manajemen Pertukaran Data Antar Kendaraan Menerapkan Protokol CoAP - Wibawa, Kadek Suar; AA. Ketut Agung Cahyawan Wiranatha; Guna Saputra (TEMATIK, 2024)
This study aims to design and develop a prototype model for inter-vehicle data exchange services using the LoRa Ra-02 Sx1278 radio module, ESP8266 microcontroller, and WiFi for internet connectivity. This system enables effective, inexpensive, and instant communication. In its implementation, we optimized simple data management to store the results of data exchanges on a database server connected to the internet using the Constraint Application Protocol (CoAP) communication protocol. The system is also capable of vehicle monitoring through a web-based application by integrating a GPS receiver. The application services and prototypes are designed to minimize costs and ease of implementation. Research and Development with a limited sample is the method applied in the development of this prototype. Testing results show that the prototype can exchange data at distances up to 500m with a success rate of 86%. The visualization of the stored vehicle location data can be monitored through the website application.